2019
DOI: 10.1007/s11676-019-01063-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different land-use systems (grazing and understory cultivation) on growth and yield of semi-arid oak coppices

Abstract: high level of agreement with self-thinning rule of − 3/2. Values for the stand density index for coppiced oak woodlands were between more than 1000 for the least disturbed (Co) and less than 400 for the most disturbed woodlands (CoCG). The structure and growth rate of the coppiced oak woodlands were irreversibly disrupted by understory tillage plus grazing and in less extent by grazing alone. It was concluded that ending undergrowth cultivation in semi-arid oak coppices should be addressed as a priority by ado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
(38 reference statements)
2
2
0
Order By: Relevance
“…In this study, with the increase of grazing intensity and spatial scale, the inter-specific relationship affinity between S. breviflora and C. songorica increased, and the inter-specific competition ability decreased. This is consistent with the results of Soltani et al , which suggest that long-term grazing generally reduces competition between dominant species (Soltani et al, 2020). The increasing affinity of the two may be interpreted as a tolerance or resistance to grazing disturbance (Levine and HilleRisLambers, 2009).…”
Section: Discussionsupporting
confidence: 92%
“…In this study, with the increase of grazing intensity and spatial scale, the inter-specific relationship affinity between S. breviflora and C. songorica increased, and the inter-specific competition ability decreased. This is consistent with the results of Soltani et al , which suggest that long-term grazing generally reduces competition between dominant species (Soltani et al, 2020). The increasing affinity of the two may be interpreted as a tolerance or resistance to grazing disturbance (Levine and HilleRisLambers, 2009).…”
Section: Discussionsupporting
confidence: 92%
“…In this study, as grazing intensity and spatial scale increased, the inter-speci c relationship a nity between S. brevi ora and C. songorica increased, and the inter-speci c competition decreased. This is consistent with the results of Soltani et al, who reported that long-term grazing changed the adaptability of the community to the environment, resulting in a decrease in the competitiveness of dominant species (Soltani et al, 2020). Only increasing the a nity of the two species can enable them to resist grazing disturbance (Levine and HilleRisLambers, 2009).…”
Section: Discussionsupporting
confidence: 92%
“…on annual tree growth should be minimized if not excluded. This can be achieved by proper sampling design and selection of appropriate trees (Soltani et al 2020). In the current study grazing, competition, and other factors could be, together with climate, responsible for the increases and Fig.…”
Section: Discussionmentioning
confidence: 99%